You're so funny Bertie Bunny - Jones, Ruby; Endersby, Frank (London : Alligator Products, Ltd., 2023)
"Bertie Bunny loves making his friends laugh. However, sometimes he becomes sad and everyone needs a friend to cheer them up!"
Primary
Keywords: Children's stories -- Pictorial works; Rabbits -- Fiction; Bunnies -- Fiction